Centros de escritura universitarios: una estrategia para la permanencia estudiantil - Zamudio Tobar, Gladys; Roldán Morales, Claudia Alexandra; Torres Tovar, Andrés Fernando; Casas Bustillo, Adriana Carolina; Montes Paz, Andrea del Pilar; Cortázar Ocampo, Evelyn; Leones Araque, Bernarda; Domínguez Anaya, Regina; Larrahondo Gómez, Mariana; Utria Machado, Leyla Esther; Andrade Gonzalez, Lina Isabel; Burbano Díaz, Camilo; et al. (Universidad Santiago de Cali, 2022)
Published